ARCHITECTURAL CONSERVATION IN AUSTRALIA, NEW ZEALAND AND THE PACIFIC ISLANDS - Stubbs, John H., author. (ABINGDON)
1 online resource
Keywords: The fourth in a series that documents architectural conservation in different parts of the world, Architectural Conservation in Australia, New Zealand and the Pacific Islands: National Experiences and Practice addresses cultural heritage protection in a region which comprises one third of the Earth's surface. In response to local needs, Australia, New Zealand and the Pacific Islands have developed some of the most important and influential techniques, legislation, doctrine and theories in cultural heritage management in the world. The evolution of the heritage protection ethos and contemporary architectural conservation practices in Australia and Oceania are discussed on a national and regional basis using ample illustrations and examples. Accomplishments in architectural conservation are discussed in their national and international contexts, with an emphasis on original developments (solutions) and contributions made to the overall field. Enriched with essays contributed from fifty-nine specialists and thought leaders in the field, this book contains an extraordinary breadth and depth of research and synthesis on the why's and how's of cultural heritage conservation. Its holistic approach provides an essential resource and reference for students, academics, researchers, policy makers, practitioners and all who are interested in conserving the built environment.